Unfitting Stories - Raoul, Valerie,Canam, Connie,Henderson, Angela D. (Wilfrid Laurier University Press, 2007)
Unfitting Stories: Narrative Approaches to Disease, Disability, and Trauma illustrates how stories about ill health and suffering have been produced and received from a variety of perspectives. Bringing together the work of Canadian researchers, health professionals, and people with lived experiences of disease, disability, or trauma, it addresses central issues about authority in medical and personal narratives and the value of cross- or interdisciplinary research in understanding such experiences. The book considers the aesthetic dimensions of health-related stories with literary readings that look at how personal accounts of disease, disability, and trauma are crafted by writers and filmmakers into published works. Topics range from psychiatric hospitalization and aestheticizing cancer, to father-daughter incest in film. The collection also deals with the therapeutic or transformative effect of stories with essays about men, sport, and spinal cord injury; narrative teaching at L'Arche (a faith-based network of communities inclusive of people with developmental disabilities); and the construction of a
Description based on publisher supplied metadata and other sources
Keywords: Literatur; Film; Krankheit